Gambaran Pengetahuan terhadap Penggunaan Obat Tanpa Resep di Desa Karangduren Kecamatan Kebonarum Kabupaten Klaten - Septyasari, Avanilla Fany; Putri, Aristhasari; Nurhaini, Rahmi; Hastikanuari, Anis Anggiara (Universitas Muhammadiyah Klaten, 2024)
Self-medication is an attempt to treat a condition or complaint based on self-diagnosed symptoms. The drugs used are non-prescription drugs, such as over-the-counter (OTC) drugs. Self-medication is one of the causes of medication errors. One of the factors in the occurrence of problems in self-medication is the lack of knowledge and understanding of the community regarding drugs and their indications. The purpose of this study was to determine the level of knowledge of the use of non-prescription drugs in the community of Karangduren Village, Kebonarum District, Klaten Regency. This research is an observational descriptive research. The sampling technique used simple random sampling method, and a questionnaire containing 15 questions including the name and content of the drug, drug efficacy, drug dosage, drug administration, and drug side effects. There were 67 respondents involved in this study. The results showed that most respondents (50.7%) had a good level of knowledge in using non-prescription drugs.